Guided implant-prosthetic rehabilitation: a clinical case report - Carlo Oddi; Giorgio Collina; Matteo Palmacci; Roberto Sgreggia; Alessia Grassi; Matteo Nagni (Annali di Stomatologia, 2023)
The advent of new assisted design software in combination with computed tomography (CT) has increased the possibility of rehabilitating edentulous jaws with implant-supported fixed prostheses, allowing flapless surgery and immediate loading even in the presence of critical bone volume. Aim: The aim of the present study is to demonstrate how the use of advanced technologies supported by specific software allows the design and execution of optimal implant surgery while going on to decrease what could be intra- and postoperative risks.